2017
DOI: 10.12783/dtssehs/hsc2016/3505
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Analysis of Physical Fitness Among Freshmen in Nanchang University

Abstract: Abstract. Objective:The purpose of this study was to investigate the general state and characteristics of physical fitness in undergraduates and to improve their physical health through effective measures. Methods: 6691 first-year students (3373 males and 3318 females) in Nanchang University participated in this study. Anthropometric measures and physical fitness tests were performed and assessed in accordance with the National student physical health standard revised in 2014 applied in China. The associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Wang ( 13 ) examined depression in university students and found that after eight weeks, painting therapy improved their depression, self-understanding, understanding of others, communication skills, and sense of responsibility. Wang ( 14 ) implemented drawing therapy in adolescents with depression and found that following the intervention negative emotions, positive emotions, and self-esteem improved.…”
Section: Introductionmentioning
confidence: 99%
“…Wang ( 13 ) examined depression in university students and found that after eight weeks, painting therapy improved their depression, self-understanding, understanding of others, communication skills, and sense of responsibility. Wang ( 14 ) implemented drawing therapy in adolescents with depression and found that following the intervention negative emotions, positive emotions, and self-esteem improved.…”
Section: Introductionmentioning
confidence: 99%